Micronutrient-rich dietary intake is associated with a reduction in the effects of particulate matter on blood pressure among electronic waste recyclers at Agbogbloshie, Ghana - Takyi, Sylvia A. (BMC Public Health, 2020)
BACKGROUND: Informal recycling of electronic waste (e-waste) releases particulate matter (PM) into the ambient air. Human exposure to PM has been reported to induce adverse effects on cardiovascular health. However, the impact of PM on the cardiovascular health of e-waste recyclers in Ghana has not been studied. Although intake of micronutrient-rich diet is known to modify these PM-induced adverse health effects, no data are available on the relationship between micronutrient status of e-waste recyclers and the reported high-level exposure to PM. We therefore investigated whether the intake of micronutrient-rich diets ameliorates the adverse effects of ambient exposure to PM(2.5) on blood pressure (BP). METHODS: This study was conducted among e-waste and non-e-waste recyclers from March 2017 to October 2018. Dietary micronutrient (Fe, Ca, Mg, Se, Zn, and Cu) intake was assessed using a 2-day 24-h recall. Breathing zone PM(2.5) was measured with a real-time monitor. Cardiovascular indices such as systolic BP (SBP), diastolic BP (DBP), and pulse pressure (PP) were measured using a sphygmomanometer. Ordinary least-squares regression models were used to estimate the joint effects of ambient exposure to PM(2.5) and dietary micronutrient intake on cardiovascular health outcomes. RESULTS: Fe was consumed in adequate quantities, while Ca, Se, Zn, Mg, and Cu were inadequately consumed among e-waste and non-e-waste recyclers. Dietary Ca, and Fe intake was associated with reduced SBP and PP of e-waste recyclers. Although PM(2.5) levels were higher in e-waste recyclers, exposures in the control group also exceeded the WHO 24-h guideline value (25 μg/m(3)). Exposure to 1 μg/m(3) of PM(2.5) was associated with an increased heart rate (HR) among e-waste recyclers. Dietary Fe intake was associated with a reduction in systolic blood pressure levels of e-waste recyclers after PM exposure. CONCLUSIONS: Consistent adequate dietary Fe intake was associated with reduced effects of PM(2.5) on SBP of e-waste recyclers overtime. Nonetheless, given that all other micronutrients are necessary in ameliorating the adverse effects of PM on cardiovascular health, nutrition-related policy dialogues are required. Such initiatives would help educate informal e-waste recyclers and the general population on specific nutrients of concern and their impact on the exposure to ambient air pollutants.